The Development of Arabic and English Language Culture in Modern Islamic Boarding Schools - Al Fajar, Adam Hafidz (Jurnal Paradigma, 2025)
This study aims to examine the development of Arabic and English language culture in modern Islamic boarding schools (pesantren) through a qualitative approach using a literature review method. The research focuses on linguistic dynamics as a form of the pesantren's adaptation to the challenges of educational globalization. Data were collected from credible written sources such as journal articles, academic books, conference proceedings, and research reports published between 2015 and 2025. The analysis process was carried out in three main stages: data reduction, thematic classification, and interpretative conclusion drawing. The findings show that the language culture of Arabic and English in modern pesantren has undergone a transformation through three phases: traditional, transitional, and modernization. Arabic, which was originally textual in nature, has expanded to become communicative, while English has been integrated as a tool for global communication. This transformation is supported by institutional strategies such as the creation of a language environment, the implementation of bilingual policies, and visionary leadership. This study makes a significant contribution to understanding the adaptive strategies of pesantren in shaping a contextual and future-oriented language culture.